Modelling the 200 m front-crawl performance predictors at the winter season peak - Costa, M.J. (2020)
This study aimed to identify potential predictors of 200 m front crawl performance at the winter season peak based on the anthropometric, physiological and biomechanical domains. Twelve expert male swimmers completed an incremental 7 × 200 m step test immediately after their most important winter competitions. Measurements were made of: (i) height, body mass and arm span as anthropometrical parameters; (ii) velocity at a 4 mmol·L-1 lactate concentration (V4), maximal oxygen uptake (VO2máx) and energy cost (C), as physiological parameters; (iii) stroke frequency (SF), stroke length (SL), stroke index (SI) and propelling efficiency (ƞp) as biomechanical indicators; and (iv) 200 m front crawl race time in official long course competitions. Spearman correlation coefficients identified V4 as the single factor having significant relationship with performance. Simple regression analysis determined V4, SI and arm span as the most relevant variables of each group. Multiple linear regression models showed that physiological factors explained better (59%) the variation in performance at this stage of the season, followed by the biomechanical (14%) ones. Therefore, V4 can be one important aspect for training control and diagnosis for those who want to achieve success in the 200 m front crawl at the winter season peak